1983
DOI: 10.1056/nejm198307283090403
|View full text |Cite
|
Sign up to set email alerts
|

Connective-Tissue Disease, Antibodies to Ribonucleoprotein, and Congenital Heart Block

Abstract: The relation between congenital heart block and maternal connective-tissue disease was studied by antibody screening of serum samples obtained in connection with 45 cases of isolated congenital complete heart block. Serum was available from 41 mothers (17 who had connective-tissue disease and 24 who were healthy) and 21 children. Thirty-four mothers had antibody to a soluble tissue ribonucleoprotein antigen called Ro(SS-A), which was identified by immunodiffusion. Anti-Ro(SS-A) was found in seven of eight seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
2
10

Year Published

1985
1985
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(162 citation statements)
references
References 21 publications
4
146
2
10
Order By: Relevance
“…This group included 3 women with 4 normal children. Three patients had SS, 2 had S S L E overlap syndrome (1 of whom had an infant with cutaneous NLE and the other had an infant with idiopathic thrombocytopenic purpura and 2 occurrences of intrauterine fetal death), and 2 were asymptomatic. Group 111 was SLE patients (n = 14) with normal children, other serologic specificities, and no detectable antibodies to LdSS-B andor RolSS-A.…”
Section: Methodsmentioning
confidence: 99%
“…This group included 3 women with 4 normal children. Three patients had SS, 2 had S S L E overlap syndrome (1 of whom had an infant with cutaneous NLE and the other had an infant with idiopathic thrombocytopenic purpura and 2 occurrences of intrauterine fetal death), and 2 were asymptomatic. Group 111 was SLE patients (n = 14) with normal children, other serologic specificities, and no detectable antibodies to LdSS-B andor RolSS-A.…”
Section: Methodsmentioning
confidence: 99%
“…Babies with NLE have maternal autoantibodies against Ro/SS-A and/or La/SS-B (1,2). Although previous immunogenetic studies have suggested that the frequencies of HLA-DR3 and DQ2 were increased among mothers of NLE infants in white and North American black populations (1,3), and a few investigators have questioned whether fetal HLA antigens are contributory, no prior study has addressed whether the maternal-fetal HLA relationship affects the immunopathogenesis of NLE.…”
Section: Neonatal Lupus Erythematosus: Haplotypic Analysis Of Hla Clamentioning
confidence: 99%
“…Anti-Ro/SS-A and anti-La/SS-B autoantibodies are amongst the few of their kind thought to be directly pathogenic: transplacental transfer of these antibodies from mother to unborn child damages the fetal cardiac conduction system resulting in congenital heart block [8,9]. Different mechanisms have been proposed to explain the development of non-organ specific autoantibodies.…”
Section: Introductionmentioning
confidence: 99%